PREVALENCIA DE LA TUBERCULOSIS BOVINA EN LA PROVINCIA DE PARINACOCHAS, AYACUCHO. - Sánchez R., Daniel (2002)
The objetive of this study was to determine the prevalence of bovine tuberculosis in 461 animals raised in small and medium farms at Parinacochas district, departament of Ayacucho, using the tuberculine intradermoreaction test. All animals resulted negative to bovine tuberculosis sugesting the absence of the disease in the area.